Guided by the Grid: Raising Attention with the Rule of Thirds. (7th February 2023) - Koliska, Michael; Oh, Klive (Soo-Kwang)
ABSTRACT: The rule of thirds is a longstanding principle that helps artists and photographers to compose aesthetically pleasing images. Despite the rule's wide use by photographers, little is known about its impact on viewers in particular to raise attention to the main subject and narrative of an image but also to possibly limit cognitive load. The findings of this exploratory, experimental study of undergraduate students at a U.S. university suggest that the rule of thirds serves as a geometric guiding structure that directs participants' vision. The rule of thirds appears to enhance participants' ease of information processing by raising attention to the predominant visual content of an image, making it more salient to the observer. Overall, the rule of thirds enabled a more correct recognition of the primary valence and the main subject or focus of interest of an image, indicating that participants may glean a better understanding of the intended message of an image. But findings also indicate significant differences between the rule of thirds composition and the placement of the main subject along the rule of thirds grid, suggesting the latter as being more effective.